Effect of Lead in Antimony and Tin Dissolution from Recycled Lead–Acid Battery Dross in Hydrobromic Acid Solution - Arturo Hirata-Miyasaki; Corby G. Anderson (Metals)
Demand and prices for antimony have increased over the last few years. Recycling supplied 15% of domestic consumption in the US, while the remaining 85% was imported. Hydrometallurgical processes have long used alkaline sulfide systems and hydrochloric acid, closing doors on new approaches. Bromine compounds have been recently used to recover PGMs and REEs successfully; thus, antimony leaching with bromine compounds is theoretically feasible. This research was conducted to develop a viable technology for hydrobromic acid between 50 °C and 70 °C as a leaching reagent on dross through single- and two-stage leaching using design of experiment (DoE) and adding sustainability to current industrial processes while minimizing waste products in recycling processes. The preliminary results showed that bromine, specifically hydrobromic acid, can be used as a leaching reagent for antimony dissolution. By decreasing the lead content in the solids and increasing the concentration, temperature, and reaction time, antimony leaching from the dross was increased from 20% to 50%. The findings, coupled with acid regeneration, can be implemented as an alternative to other reagents in industrial plants.